PENGARUH INFLASI, SUKU BUNGA, NILAI TUKAR, DAN PRODUK DOMESTIK BRUTO TERHADAP NILAI PERUSAHAAN - Dewi Sartika, Umi; Choiriyah, Choiriyah; Siddik, Sa’adah (Jurnal Ilmu Manajemen, 2019)
The problem of this study is whether there is the influence of inflation, interest rates, exchange rates and gross domestic product on the value of the company in the textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The results of the study concluded, first, inflation has a negative effect, it states that inflation is inversely related to the value of the company with inflation. Second, interest rates, exchange rates and gross domestic product have a positive influence on the value of the company. The third is an increase in the value of the company, so there is also an increase in interest rates, exchange rates and gross domestic product, and vice versa. Third, inflation, interest rates, exchange rates, and gross domestic product partially influence the value of the company in the textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2012-2017 simultaneously and have a positive and significant effect on the value of companies in manufacturing companies. Textiles and Garments Registered on the Indonesia Stock Exchange. Fourth, inflation, interest rates, exchange rates, and gross domestic product jointly affect the value of the company in the Textile Subsector and Garment Manufacturing Companies Listed on the Indonesia Stock Exchange.